1/ƒ noise for intermittent quantum dots exhibits nonstationarity and critical exponents - Sadegh, Sanaz, author; Barkai, Eli, author; Krapf, Diego, author; IOP Publishing Ltd., publisher (Colorado State University. Libraries, 2014)
The power spectrum of quantum dot (QD) fluorescence exhibits 1/ƒ β noise, related to the intermittency of these nanosystems. As in other systems exhibiting 1/ƒ noise, this power spectrum is not integrable at low frequencies, which appears to imply infinite total power. We report measurements of individual QDs that address this long-standing paradox. We find that the level of 1/ƒ β noise decays with the observation time. The change of the spectrum with time places a bound on the total power. These observations are in stark contrast with most measurements of noise in macroscopic systems which do not exhibit any evidence for non-stationarity. We show that the traditional description of the power spectrum with a single exponent β is incomplete and three additional critical exponents characterize the dependence on experimental time.
Keywords: nanocrystals; 1/ƒ noise; power spectrum; blinking